2020
DOI: 10.1113/ep088571
|View full text |Cite
|
Sign up to set email alerts
|

The effects of high altitude ascent on splenic contraction and the diving response during voluntary apnoea

Abstract: Voluntary apnoea causes splenic contraction and reductions in heart rate (HR; bradycardia), and subsequent transient increases in haemoglobin concentration ([Hb]). Ascent to high altitude (HA) induces systemic hypoxia and reductions in oxygen saturation (S pO 2), which may cause tonic splenic contraction, which may contribute to haematological acclimatization associated with HA ascent. We measured resting cardiorespiratory variables (HR, S pO 2 , [Hb]) and resting splenic volume (via ultrasound) during increme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 72 publications
4
17
0
Order By: Relevance
“…The stepwise response when superimposing and removing exercise to a hypoxic stimulus shows that the spleen response is graded and likely able to fine-tune the amount of circulating red cells to meet the oxygen demands in the short term. This effect has been suggested by several of our previous field studies (Richardson et al 2007;Schagatay et al 2020;Holmström et al 2021a, b). However, in those studies, the hypoxic stimulus was chronic and it could not be ruled out that other changes affected baseline hemoglobin concentration (Hb; e.g., elevations due to dehydration or induced by enhanced erythropoiesis) and possibly spleen size.…”
Section: Dear Editormentioning
confidence: 84%
See 1 more Smart Citation
“…The stepwise response when superimposing and removing exercise to a hypoxic stimulus shows that the spleen response is graded and likely able to fine-tune the amount of circulating red cells to meet the oxygen demands in the short term. This effect has been suggested by several of our previous field studies (Richardson et al 2007;Schagatay et al 2020;Holmström et al 2021a, b). However, in those studies, the hypoxic stimulus was chronic and it could not be ruled out that other changes affected baseline hemoglobin concentration (Hb; e.g., elevations due to dehydration or induced by enhanced erythropoiesis) and possibly spleen size.…”
Section: Dear Editormentioning
confidence: 84%
“…Concerning the combined effects of high altitude hypoxia with other stimuli, we found in a previous study where we examined exercise at different altitudes, that resting spleen volume was reduced with incremental ascent and spleen volume was further reduced with exercise at all altitudes, while Hb values changed in the opposite direction (Schagatay et al 2020). In another study, wherein apnea was implemented to induce spleen contraction at different altitudes (Holmström et al 2021a;b), we observed a similar stepwise more-pronounced tonic spleen contraction with incremental ascent, but also here another stimulusapnea-in general added to the contraction, attesting to a tonic splenic contraction of about − 14%/1000 m of ascent. The phenomenon was in fact noted already in 2007 in a study only measuring Hb (Richardson et al 2007).…”
Section: Dear Editormentioning
confidence: 96%
“…These methodological challenges include caudal movements during deep inspiration, changes in intra-abdominal pressure and overlapping of the spleen with the diaphragm, and rib cage, likely due to splenic excursions within the abdominal cavity during vigorous cycling bouts. Overall, these factors preclude adequate visualization of the spleen, and in particular spleen thickness, which is often measured by others (Schagatay E et al 2020 ; Holmström et al 2021 ). However, this may further complicate attempts to capture spleen size via a single image during aerobic exercise.…”
Section: Discussionmentioning
confidence: 99%
“…In healthy humans, the spleen plays an important role in oxygen transport during apnea (Bakovic et al 2003 ; Bouten et al 2019 ; Palada et al 2007 ), and exposure to high altitude (Holmström et al 2021a ), primarily due to its ability to contract and release additional red blood cells (RBC’s) into the systemic circulation (Espersen et al 2002 ). Early work by Allsop et al ( 1992 ) showed that after a brief period of exercise, the RBC exit the spleen within ~ 60 s, and the spleen emptying transiently increases RBC concentrations in the systemic circulation.…”
Section: Introductionmentioning
confidence: 99%
“…Acclimatisation a powerful way of ameliorating the negative physiological and pathophysiological responses to altitude. The paper by Leacy and colleagues investigates the extent to which hysteresis in steady‐state cardiorespiratory variables can quantify ventilatory acclimatization to high altitude (Leacy et al., 2021), while Holmström and colleagues consider the contribution of splenic contraction early in acclimatization (Holmström et al., 2021).…”
mentioning
confidence: 99%